Fabrication of FRP/CNT hybrid laminate composites and their effect on interlaminar and mechanical properties - Mateo Duarte; Johan A. Oquendo; Sebastián Vallejo; Johnattan Vargas; Yamile Cardona-Maya; Cesar A. Isaza (AIMS Materials Science)
Composites are widely used in different areas of engineering due to their remarkable mechanical properties; however, it has been evidenced that laminated composites exhibit certain vulnerabilities, particularly in interlaminar regions, which can lead to failures. To address this issue, efforts have been made to enhance interlaminar strength, with one notable approach being the incorporation of nano-reinforcements that serve as bridges between the laminate layers. Among these nano-reinforcements, carbon nanotubes (CNTs) have emerged as a highly promising material to mitigate the deficiencies in interlaminar zones. Despite their potential, integrating CNTs into structural laminates presents significant challenges. This research focuses on developing a strategy to effectively incorporate well-dispersed multi-walled carbon nanotubes (MWCNTs) into structural laminate composites to enhance interlaminar toughness. The study explored three different processes for integrating MWCNTs: hand lay-up, vacuum bagging, and liquid resin infusion, each with varying percentages of MWCNT addition. The aim was to determine the most efficient method for achieving uniform dispersion and improved mechanical properties. The results of this investigation demonstrated that well-dispersed MWCNTs significantly enhance the interlaminar and overall mechanical properties of composites. Each method showed varying degrees of success, but the overarching conclusion is clear: MWCNTs, when properly integrated, offer a viable solution to the inherent weaknesses of laminated composites. This advancement holds substantial promise for the future of composite materials, particularly in applications requiring enhanced durability and strength. The findings pave the way for further research and development in optimizing nano-reinforcement techniques, ultimately contributing to the creation of more robust and reliable composite structures.